Belarus’ Sovereignty in Question: Assessing its de facto Sovereign Status in the Shadow of Russia - Molis, Arūnas; Pastorello, Sara (Politologija, 2024)
The paper explores state sovereignty by developing a systematic framework for categorising states based on their sovereignty status. At the heart of our analysis lies the distinction between sovereign states and satellite states – a distinction that has significant implications for global security, stability, and the balance of power. While sovereign states exercise full autonomy and control over their affairs, satellite states often find themselves in a subordinate position, heavily influenced or even dominated by external powers. A theoretical framework deconstructs the concept of sovereignty into four crucial elements: authority, legitimacy, independence, and territoriality, which provide a structured assessment of the level of sovereignty in a state and serve as the basis for our analysis. To illustrate the application of our framework, we adopt a case study approach focused on Belarus. As a nation situated at the crossroads of Eastern Europe with a history marked by geopolitical contestation and strategic manoeuvring, Belarus provides a compelling context for examining sovereignty dynamics. Through a systematic analysis of Belarus’ political, economic, and military landscape, we seek to assess its sovereignty status within the framework of our analysis. While the topic of Belarus’ sovereignty and integration within Russia has been extensively explored over the years, the innovative contribution of this paper lies in purposefully designed methodology for sovereignty assessment and the use of the latest empirical data while practically applying the model for the case of Belarus.